Metaphorical Expression of the Word Anger in the Corpus of Contemporary of American English (COCA) - Kartika Sari, Dewa Ayu; Aryawibawa, I Nyoman; Sri Rahayuni, Ni Ketut (Humanis; Vol 22 No 4 (2018)DO - 10.24843/JH.2018.v22.i04.p07, 2018)
Metaphors are used to create poetic impression in poems or poetry. However, linguist disagree this idea and they believe that metaphors are not used for language style of poems or poetry only, but they believe that people also use them in their daily language. This study is entitled Metaphorical Expression of the Word Anger in the Corpus of Contemporary of American English (COCA) . The data source was taken from corpus of contemporary American English (COCA) using keyword of anger in Keyword in the Context (KWIC) as the main data. The theories used in this study were theory proposed by Lakoff & Johnson (1998) to identify the conceptual metaphor, Pragglejaz’s MIP (Metaphor Identification Procedure) and Steen’s five steps to identify the metaphor in the context. The result shown that all conceptual metaphors were found in this study, such as structural metaphor, orientational metaphor, ontological metaphor and personification.